2010 IEEE Global Telecommunications Conference GLOBECOM 2010 2010
DOI: 10.1109/glocom.2010.5683130
|View full text |Cite
|
Sign up to set email alerts
|

A 3-D Markov Chain Model for a Multi-Dimensional Indoor Environment

Abstract: In this paper, a pico-cellular airport traffic model is proposed which supports Engset distributed fresh call arrival process and General distributed handoff process with Dynamic Channel Allocation (DCA). The proposed model enables load balancing using DCA and uses a three-dimensional Markov chain to compute traffic congestion and call congestion for any kind of traffic streams, including Pure Chance Type-I (PCT-I) or Pure Chance Type-II (PCT-II). The application of the proposed model is illustrated in assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Both numerical and simulation results have shown that the FSMC channel model provides an accurate model for the real channels. Based on a three-dimensional Markov chain model, a pico-cellular airport traffic model was proposed in [12] which models Engset distributed fresh call arrival process and the general distributed handoff process with dynamic channel allocation. The energy efficiency of fixed-rate transmissions from Markov sources over Rayleigh fading channels was investigated in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Both numerical and simulation results have shown that the FSMC channel model provides an accurate model for the real channels. Based on a three-dimensional Markov chain model, a pico-cellular airport traffic model was proposed in [12] which models Engset distributed fresh call arrival process and the general distributed handoff process with dynamic channel allocation. The energy efficiency of fixed-rate transmissions from Markov sources over Rayleigh fading channels was investigated in [13].…”
Section: Introductionmentioning
confidence: 99%
“…A newly proposed three‐dimensional (3D) Markov chain model for indoor applications and LTE femtocell are also discussed in [14, 15], respectively, which are required to define priority in the HO algorithm. On the other hand, different mobility patterns and dynamic network conditions might cause challenging situation for MUs, despite femtocells' capability of providing services in shadowed areas by cell coverage enhancements.…”
Section: Related Workmentioning
confidence: 99%
“…Seamless handover is planned and simulated in [13] by reactively multicasting the data to both the source and target cells after the handover is actually initiated, which results in a reduction in the downlink service interruption time, as well as avoiding the packet loss compared to the standard 3GPP, with only limited extra requirements. Newly proposed 3-D Markov Chain model for indoor applications and LTE femtocell are also discussed in [14], [15] respectively, which are required to define priority in the handover algorithm. On the other hand, different mobility patterns and dynamic network conditions might cause challenging situation for mobile users, despite femtocells capability of providing services in shadowed areas by cell coverage enhancements.…”
Section: Related Workmentioning
confidence: 99%